AI-driven disinformation: policy recommendations for democratic resilience - Romanishyn, Alexander; Malytska, Olena; Goncharuk, Vitaliy (Frontiers in Artificial Intelligence, 2025)
The increasing integration of artificial intelligence (AI) into digital communication platforms has significantly transformed the landscape of information dissemination. Recent evidence indicates that AI-enabled tools, particularly generative models and engagement-optimization algorithms, play a central role in the production and amplification of disinformation. This phenomenon poses a direct challenge to democratic processes, as algorithmically amplified falsehoods systematically distort political information environments, erode public trust in institutions, and foster polarization – conditions that degrade democratic decision-making. The regulatory asymmetry between traditional media – historically subject to public oversight – and digital platforms exacerbates these vulnerabilities. This policy and practice review has three primary aims: (1) to document and analyze the role of AI in recent disinformation campaigns, (2) to assess the effectiveness and limitations of existing AI governance frameworks in mitigating disinformation risks, and (3) to formulate evidence-informed policy recommendations to strengthen institutional resilience. Drawing on qualitative analysis of case studies and regulatory trends, we argue for the urgent need to embed AI-specific oversight mechanisms within democratic governance systems. We recommend a multi-stakeholder approach involving platform accountability, enforceable regulatory harmonization across jurisdictions, and sustained civic education to foster digital literacy and cognitive resilience as defenses against malign information. Without such interventions, democratic processes risk becoming increasingly susceptible to manipulation, delegitimization, and systemic erosion.